Prognostic factors of thalamic and thalamopeduncular low-grade gliomas in children: A systematic review and recommendations for surgical management - Jana Táborská; Adéla Bubeníková; Petr Skalický; Jakub Táborský; David Horváth; Michal Zápotocký; Ondřej Bradáč; Vladimír Beneš, 3rd (Brain and Spine)
Introduction: Pediatric low-grade gliomas arising from the thalamus or thalamopeduncular junction are rare. Prognostic factors are thus seldom reported in the literature. Research question: This systematic review aims to define the factors influencing the prognosis of pediatric patients with thalamic and thalamopeduncular low-grade gliomas. Material and methods: An extensive literature search in adherence to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was performed and included Web of Science, Scopus, and OVID interface (Medline and Embase). Original articles were selected if they provided data on 10 or more patients under 18 years old with separate or retrievable data for thalamic or thalamopeduncular low-grade gliomas, as well as at least one prognostic factor and its corresponding outcome. The risk of bias and applicability were assessed using The Quality Assessment of Prognostic Accuracy Studies criteria. Results: The study selection process resulted in the inclusion of 14 articles out of the initial pool of 876 references. These 14 articles encompassed data from 446 patients. The prognostic factors reported were the extent of resection in ten studies, age and radiotherapy in four studies, bilateral involvement and molecular genetics in two studies, and sex and dissemination in one study each. Significant prognostic factors included the extent of resection, bilateral involvement, histology, and radiotherapy. Discussion and conclusion: The reported factors considered significant for prognosis align with previously published data. The maximal safe resection, as a potentially curative modality for thalamic low-grade glioma, and the multidisciplinary approach to each patient should be a standard of care. Given the excellent long-term outlook of these patients, the extent of resection should not be pursued at the risk of neurological function since additional therapeutic possibilities are available today, such as molecular-targeted agents.